2020
DOI: 10.1016/j.aquaeng.2019.102042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gas to liquid ratio on carbon dioxide removal and heat loss across a forced ventilated trickling filter

Abstract: The objective of this study was to investigate the effect of the gas : liquid ratio (GLR) on carbon dioxide removal and heat loss across a forced-ventilated trickling filter (TF) used as bioreactor. The effect of 8 different GLRs (1.2-15.7) on carbon dioxide removal and heat loss from water passing a TF were tested in random order. The TF was part of a pilot scale fresh water intensive recirculating aquaculture system and had a media bed height of 1.8m, a diameter of 0.9m, a specific surface area of 200 m 2 /m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In a TF, water is pumped to the top of the filter, where gravity pulls the water down through the filter medium (Figure 3) [53]. The medium can be unstructured/structured polyethylene [54], wood wool/sawdust [55], constructed wetland [56], or other materials that break up the flow of water. Aeration of the water in 5 of 12 combination with an air stream in the direction opposite to the flow of water (caused by a fan) allows CO 2 to diffuse from the water to the surrounding air.…”
Section: Trickling Filter and Recirculation Aquaculture Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a TF, water is pumped to the top of the filter, where gravity pulls the water down through the filter medium (Figure 3) [53]. The medium can be unstructured/structured polyethylene [54], wood wool/sawdust [55], constructed wetland [56], or other materials that break up the flow of water. Aeration of the water in 5 of 12 combination with an air stream in the direction opposite to the flow of water (caused by a fan) allows CO 2 to diffuse from the water to the surrounding air.…”
Section: Trickling Filter and Recirculation Aquaculture Systemsmentioning
confidence: 99%
“…It is then usually pumped outside away from the facility. In 2020, Karimi et al tested the ability of a Bionet-filled trickling filter to remove CO 2 under different gas-to-liquid ratios (GLRs) [54]. They found that a GLR of 5:1 was the most cost-effective setup for their RAS, decreasing the [CO 2 ] from 7.2 to 5.1 mg/L.…”
Section: Trickling Filter and Recirculation Aquaculture Systemsmentioning
confidence: 99%
See 1 more Smart Citation